Deep lamellar keratoplasty with complete removal of pathological stroma for vision improvement - Sugita, J. (1997)
AIMS/BACKGROUND—Deep lamellar keratoplasty (DLK) was performed to restore visual acuity in 120 eyes with corneal stromal opacification. DLK is believed to be an effective treatment in eyes in which endothelial cell function had been preserved, and in which there was no epithelial or stromal oedema. The purpose of this study was to evaluate the effectiveness of this treatment. METHODS—The stroma was excised to the extent that only Descemet's membrane remained, at least in the optical zone. Donor corneas of full, or almost full, thickness with Descemet's membrane removed, or which had been lathed to a thickness of 0.4 mm from the endothelial side, were attached by suturing. RESULTS—In 113 eyes which were observed for 6 months or more postoperatively in which average prospective visual acuity was 0.09,( )average postoperative visual acuity improved to 0.6. Specular microscopy 1 month postoperatively revealed average endothelial cell counts of 2225 (SD 659)/mm(2), while 24 months postoperatively this value was 1937 (642)/mm(2) (cell loss 13%). Puncturing of Descemet's membrane during surgery occurred in 47 of 120 eyes (39.2%), but after 12 months, there was no difference in visual acuity or number of endothelial cells between these eyes and those in which no puncturing had occurred. CONCLUSIONS—There was no postoperative endothelial rejection reaction with DLK, and restoration of postoperative visual acuity was quite adequate. Compared with penetrating keratoplasty, DLK allows endothelial cell counts to be maintained for a longer period. In addition, results can be expected to be more consistent over the long term with DLK.